Vote! - Christelow, Eileen (New York : Clarion Books, 2003)
Using a campaign for mayor as an example, shows the steps involved in an election, from the candidate$1 (Bs speeches and rallies, to the voting booth where every vote counts, to the announcement of the winner.s
Keywords: Voting -- United States -- Juvenile literature; Elections -- United States -- Juvenile literature; Political campaigns -- United States -- Juvenile literature; Voting; Elections; Politics, Practical